2022
DOI: 10.3390/ma15031149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mechanical Deformations on the Characteristic Impedance of Sewed Textile Signal Lines

Abstract: The following article describes a new type of textile signal line that can be used in smart clothing. The article presents the structure of this line and the materials used for its construction. The article also presents the results of research on the influence of the line tensile force on the value of its characteristic impedance. The above tests were carried out on lines where the electrically conductive paths do not have the form of straight lines, as is often the case in smart clothing. The article also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It was observed that the flow stress of the 9310 steel decreased with an increase in the deformation temperature or a decrease in the strain rate. Kubiak and Lesnikowski [ 35 ] investigated the influence of mechanical deformation on the characteristic impedance of sewed textile signal lines (TSLs). Regardless of the tensile forces, only the substrate weave was found not to affect the characteristic impedance change.…”
mentioning
confidence: 99%
“…It was observed that the flow stress of the 9310 steel decreased with an increase in the deformation temperature or a decrease in the strain rate. Kubiak and Lesnikowski [ 35 ] investigated the influence of mechanical deformation on the characteristic impedance of sewed textile signal lines (TSLs). Regardless of the tensile forces, only the substrate weave was found not to affect the characteristic impedance change.…”
mentioning
confidence: 99%